Peculiarity in crystal packing of anti‐HIV lectin actinohivin in complex with α(1–2)mannobiose. (25th September 2013) - Suzuki, Kaoru; Tsunoda, Masaru; Hoque, M. Mominul; Zhang, Fang; Jiang, Jiandong; Zhang, Xiaoxue; Ohbayashi, Naomi; Tanaka, Haruo; Takénaka, Akio
<x xml:space="preserve">Abstract</x> Previously, the anti‐HIV lectin actinohivin (AH) was cocrystallized with the target α(1–2)mannobiose (MB) in the apparent space group P213. However, three MB‐bound AH rotamers generated by ±120° rotations around the molecular pseudo‐threefold rotation axis are packed randomly in the unit cell according to P212121 symmetry [Hoque et al. (2012). Acta Cryst. D68, 1671–1679]. It was found that the AH used for crystallization contains short peptides attached to the N‐terminus [Suzuki et al. (2012). Acta Cryst. F68, 1060–1063], which cause packing disorder. In the present study, the fully mature homogeneous AH has been cocrystallized with MB into two new crystal forms at different pH. X‐ray analyses of the two forms reveal that they have peculiar character in that the space groups are the same, P22121, and the unit‐cell parameters are almost the same with the exception of the length of the a axis, which is doubled in one form. The use of homogeneous AH resulted in the absence of disorder in both crystals and an improvement in the resolution, thereby establishing the basis for AH binding to the target MB. In addition, the two crystal structures clarify the interaction modes between AH molecules, which is important knowledge for understanding the multiple binding effect generated when two AH molecules are linked together with a short peptide [Takahashi et al. (2011). J. Antibiot.64, 551–557].